Performance, self-representation and narrative: Interviewing with video / Transl. by A.V. Pechurina, A.V. Kolosov (Социологический журнал, 2007)
A short translation of the article of British scientist Sarah Pink (Pink S. Performance, self-representation and narrative: Interviewing with video. Seeing is Believing? Approaches to visual research. Studies in qualitative methodology. Vol. 7 Ed. by C. Pole. L.: Elseiver Science, 2004), made by A.V. Pechurina and A.V. Kolosov, is represented. The article discusses the method of video-interview, which was specifically designed by Sarah Pink to use in her study of different components and elements of “sensory home”. The article focuses on various strategies of self-narrative and self-presentation utilised by participants during the interview with a video camera. Specifically, Pink discusses three key narratives that emerged in the context of her study and which she refers to as the “Hello magazine”, “estate agent”, and “self-analysis” narratives. Using these narratives Pink critically evaluates the nature of the ethnographic method and the potential use of the participatory visual element within it linking this discussion to concepts of gender, performance, and the media. As Pink argues, the presence of a video camera reveals the complexity of common understanding of contemporary media culture and affects the way the ethnographic knowledge is presented to a researcher by research participants.